Development of the Entrepreneurial University-Business Strategic Interaction Model for Kazakhstan - Drakh, T.P.; Salzhanova, Z.A.; Borisova, E. (BUKETOV BUSINESS REVIEW, 2021)
Object: The object of this study is the development of university-business strategic interaction model on the basis of analysis of theoretical studies of the organizational and economic mechanism, its essence, structure and elements, as well as models of interaction of shareholders in the process of their evolution. Methods: The historical, informational and comparative analysis methods have been used for the study. The structural-functional and axiomatic methods, systematic approach have been applied to develop the main provisions and conclusions. Results: The article presents the results of the analysis of theoretical concepts and approaches describing the organizational and economic mechanisms, and university-business interaction models, as well as the university-business strategic interaction models developed by the authors. Conclusions: To increase the effectiveness of the interaction of universities with business, it is necessary to find common points of contact of their interests, which launch the interaction mechanism.